Unravelling Contributions of Astrocytic Connexin 43 to the Functional Activity of Brain Neuron–Glial Networks under Hypoxic State In Vitro - Tatiana A. Mishchenko; Roman S. Yarkov; Mariia O. Saviuk; Mikhail I. Krivonosov; Alexey D. Perenkov; Sergey V. Gudkov; Maria V. Vedunova (Membranes, 2022)
Brain hypoxia remains an Achilles’ heel for public health that must be urgently addressed. Hypoxic damage affects both neurons and glial cells, particularly astrocytes, which are in close dynamic bi-directional communication, and are organized in plastic and tightly regulated networks. However, astroglial networks have received limited attention regarding their influence on the adaptive functional rearrangements of neural networks to oxygen deficiency. Herein, against the background of astrocytic Cx43 gap junction blockade by the selective blocker Gap19, we evaluated the features of spontaneous calcium activity and network characteristics of cells in primary cultures of the cerebral cortex, as well as the expression levels of metabotropic glutamate receptors 2 (mGluR2) and 5 (mGluR5) in the early and late periods after simulated hypoxia in vitro. We showed that, under normoxic conditions, blockade of Cx43 leads to an increase in the expression of metabotropic glutamate receptors mGluR2 and mGluR5 and long-term modulation of spontaneous calcium activity in primary cortical cultures, primarily expressed in the restructuring of the functional architectonics of neuron–glial networks through reducing the level of correlation between cells in the network and the percentage of existing correlated connections between cells. Blocking Cx43 during hypoxic injury has a pronounced neuroprotective effect. Together with the increased expression of mGluR5 receptors, a decrease in mGluR2 expression to the physiological level was found, which suggests the triggering of alternative molecular mechanisms of cell adaptation to hypoxia. Importantly, the blockade of Cx43 in hypoxic damage contributed to the maintenance of both the main parameters of the spontaneous calcium activity of primary cortical cultures and the functional architectonics of neuron–glial networks while maintaining the profile of calcium oscillations and calcium signal communications between cells at a highly correlated level. Our results demonstrate the crucial importance of astrocytic networks in functional brain adaptation to hypoxic damage and could be a promising target for the development of rational anti-hypoxic therapy.